Degraded Environments Alter Prey Risk Assessment - Lönnstedt, Oona M (Blackwell Publishing Ltd, 2013)
Elevated water temperatures, a decrease in ocean pH, and an increasing prevalence of severe storms have lead to bleaching and death of the hard corals that underpin coral reef ecosystems. As coral cover declines, fish diversity and abundance declines. How degradation of coral reefs affects behavior of reef inhabitants is unknown. Here, we demonstrate that risk assessment behaviors of prey are severely affected by coral degradation. Juvenile damselfish were exposed to visual and olfactory indicators of predation risk in healthy live, thermally bleached, and dead coral in a series of laboratory and field experiments. While fish still responded to visual cues in all habitats, they did not respond to olfactory indicators of risk in dead coral habitats, likely as a result of alteration or degradation of chemical cues. These cues are critical for learning and avoiding predators, and a failure to respond can have dramatic repercussions for survival and recruitment.